Vector-borne diseases and economic activity: Evidence from historical farmer productivity in the US - Maurizio Malpede (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2020)
This study provides an estimation of the causal relationship between the reduction in malaria transmission and farmer agricultural productivity. Exploiting exogenous geographic variations in the stability of malaria and using historical disaggregated county data for the US together with a robust quasi-experimental approach, I show that the eradication of malaria led to approximately one fifth of the farmer agricultural productivity growth in the US. Using historical spatial data on cropland distribution within the US, I also show that the positive effect was entirely due to better health conditions rather than a greater availability of arable land. No effect is found on agricultural output per capita for more endemic counties, suggesting that the increase in farm output was compensated by the increase in population. Robustness checks from geographic variations in malaria stability within neighboring counties along with placebo treatments reinforce the positive effect of the eradication of malaria in the US on farmer agricultural productivity.
Keywords: I15; N31; N32; O13; Q12; 330; Malaria; Natural Resources; Agricultural Productivity